Do protected areas in Panama support intact assemblages of ungulates? - Meyer, Ninon; Moreno, Ricardo; Sanches, Edgar; Ortega, Josue; Brown, Elliot; Jansen, Patrick A. (THERYA, 2016)
Ungulates play an essential role in terrestrial ecosystems, but suffer from hunting and habitat degradation which often results in their decline. Panama harbors five species of ungulate and is an important portion of the Mesoamerican Biological Corridor, but its forest habitat and its fauna are currently threatened. Protected areas have been designated to preserve the biodiversity, but studies evaluating their effectiveness in maintaining ungulates are lacking in Panama. In this study we used camera-trapping surveys to determine the occurrence and abundance of the ungulate species in 13 protected areas across Panama. There were large differences in the ungulate communities among the sites we surveyed. Some sites were impoverished with just one ungulate species recorded while just a single site harbored all five species. The white-lipped peccary was the rarest species and the collared peccaries the most common, captured in all the sites. Moreover, we found large variation in ungulate abundance across the sites. Our results indicate that few protected areas in Panama effectively maintain the entire assemblage of ungulate species.